Integrating Primary Care and Specialized Therapies in Rheumatoid Arthritis: Optimizing Recognition, Management, and Referral Practices - Dimitrina Miteva; Konstantina Bakopoulou; Ivan Padjen; Issa El Kaouri; Latchezar Tomov; Georgi V. Vasilev; Russka Shumnalieva; Tsvetelina Velikova (Rheumato)
Rheumatoid arthritis (RA) is an immune-mediated chronic and long-term condition that can lead to severe joint damage and disability. It has been shown that doctor–patient interaction and communication can have a significant impact on faster patient diagnosis and treatment outcomes. Primary care (PC) is the first level of patient contact with doctors and the health system. Communication between them is often ineffective, leading to delays in diagnosis, care, and the use of disease-modifying antirheumatic drugs (DMARDs). The protocols and standards for the treatment of RA are well established by all rheumatology organizations. All of them recommend early initiation of DMARDs, which leads to better long-term outcomes. There are some recommendations that would lead to better optimization of recognition, management, and referral practices. Early diagnosis, effective communication between general practitioners and specialists, and patient education about possible targeted therapies and biological products, as well as subsequent monitoring of therapies and screening for risk factors and comorbidities, will improve patient health and optimize costs. We aimed to offer strategies and possibilities for integrating and optimizing primary care and specialized therapies in RA because proper management will reduce the severity of the disease and even reduce mortality from chronic diseases such as RA.